How Are Patented AI, Software and Robot Technologies Related to Wage Changes in the United States? - Fossen, Frank M.; Samaan, Daniel; Sorgner, Alina (Frontiers in Artificial Intelligence, 2022)
We analyze the relationships of three different types of patented technologies, namely artificial intelligence, software and industrial robots, with individual-level wage changes in the United States from 2011-2021. The aim of the study is to investigate if the availability of AI technologies is associated with increases or decreases in individual workers’ wages and how this association compares to previous innovations related to software and industrial robots. Our analysis is based on indicators extracted by Webb (2020) from the text of patents to measure the exposure of occupations to these three types of technologies. We combine data on individual wages for the United States with the new technology measures and regress individual annual wage changes on these measures controlling for a variety of other factors. Our results indicate that innovations in software and industrial robots are associated with wage decreases, possibly indicating a large displacement effect of these technologies on human labor. On the contrary, for innovations in AI, we find wage increases, which may indicate that productivity effects and effects coming from the creation of new human tasks are larger than displacement effects of AI. AI exposure is associated with positive wage changes in services, whereas exposure to robots is associated with negative wage changes in manufacturing. The relationship of the AI exposure measure with wage increases has become stronger in 2016-2021 in comparison to the five years before.